Development of an Empirically-Based Risk Assessment Instrument - (:unkn) unknown (My University, 2016)
In 2001, the Urban Institute was commissioned by the District of Columbia Pretrial Services Agency (PSA) to develop a risk assessment instrument to assist its diagnosticians in recommending conditions of pretrial release for the thousands of defendants they process each year. This is the final report on the second and final phase of the instrument development. This phase of the research built on the earlier work by extending the period for observing outcomes by 14 months (from nearly two years to three years or longer), expanding the set of predictor items considered for inclusion on the instrument, and searching for combinations of items for inclusion.